Spatial-temporal evolution of plateau and plain lakes and climate driving factors based on Google Earth Engine platform - Guo, Qiaozhen; Yang, Guang; Wu, Xiaoxu; Jin, Huiyi; Tian, Yaxin (Frontiers in Environmental Science, 2024)
Accurate understanding of lake water dynamic changes is beneficial to sustainable utilization of water resources and maintenance of ecological balance. Lake change is sensitively reflective of climate and environment change. This study chooses plateau lake and plain lake as the study area, and uses Landsat TM/ETM+/OLI and meteorological data as data source. Based on the Google Earth Engine platform, lake areas are extracted using NDWI method, and lake morphological characteristics are analyzed. The model between climate factors and lake area is established and analyzed in sections according to the difference of lake change trend. The results indicate that the morphological characteristic index of the plateau lakes changes little, but that of the plain lakes changes greatly. Precipitation in the plain lakes fluctuates more violently than that in the plateau lakes. The temperature fluctuation in the plateau lakes is larger than that in the plain lakes.